Manajemen Pendidikan Karakter dalam Pembentukan Akhlak di UPT SMPN 5 Gresik dan SMP Muhammadiyah 7 Gresik - Muafifah Muafifah; Taufiq Haris; A. Faizin (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to describe and analyze the implementation of Character Education Management (MPK), identify influencing factors, and analyze the implications of MPK implementation on the formation of students' morals at UPT SMPN 5 Gresik and SMP Muhammadiyah 7 Gresik. This research uses a descriptive qualitative approach with a multi-site case study design. Data collection was carried out through in-depth interviews, participatory observation, and documentation study. The results showed that: (1) MPK in both schools is implemented systematically through the functions of planning, organizing, actuating, and controlling. UPT SMPN 5 Gresik integrates the values of the Pancasila Student Profile, while SMP Muhammadiyah 7 Gresik emphasizes the internalization of ISMUBA (Al-Islam, Kemuhammadiyahan, and Arabic) values through a boarding school pattern; (2) The main supporting factors are the visionary exemplary of the Principal and teacher synergy, while the inhibiting factors include the asymmetry of parenting styles and the negative impact of gadgets; (3) The implications of MPK proved significant in increasing discipline, spiritual piety in worship, and strengthening social etiquette by decreasing the rate of bullying in the school environment